Altering Neighborhood Relatedness and Species Composition Affects Interior Douglas-Fir Size and Morphological Traits With Context-Dependent Responses - Asay, Amanda K.; Simard, Suzanne W.; Dudley, Susan A. (Frontiers in Ecology and Evolution, 2020)
Trees often exist in a complex ecological system with many biological interactions. Here we examine kin interactions of Pseudotsuga menziesii var. glauca (interior Douglas-fir) both in the context of pure kin stands, in accordance with established plant kin selection and recognition studies, but also in combination with inter and intraspecific neighbors in order to observe how interactions may differ in a more complex system. Seedlings grown with kin neighbors (i.e. in stands that contained only kin) were significantly larger (biomass, height and root length) than those grown with any type of unrelated neighbor. However, of those with an unrelated neighbor, performance was better if that neighbor was interspecific (lodgepole pine rather than a stranger, or non-kin, Douglas-fir neighbor). Interestingly when Douglas-fir was grown in mixed stands, the four growth and four morphological traits of the seedlings examined paralleled neither pure stranger nor pure kin stands. This suggests that a mixed stand environment yielded cues that were uniquely different than either type of pure stand and that these seedlings are able to integrate that information and respond in a different way; for example, with increased early mycorrhizal fungal colonization. The morphological traits fine: coarse root allocation and slenderness (height relative to diameter) closely paralleled the seeding-size results, with the greatest values in pure kin stands. Whereas, fine root: needle allocation showed a kin response of less fine root allocation relative to needle mass compared to strangers, but kin seedlings had more fine root allocation when grown with a pine compared to a stranger Douglas-fir neighbor. We have demonstrated that the kin response in Douglas-fir is influenced by the complexity of the environment in which it grows, and this has significant effects on growth, morphology and mycorrhizal fungal colonization that may affect the success and resiliency of regeneration.